ANALISIS PENGARUH BRAND EXPERIENCE TERHADAP REVISIT INTENTION PADA HOTEL SANTIKA PREMIERE ICE BSD CITY - Jennifer Jennifer; Roozana Maria Ritonga (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Brands are important in this competitive era where brands exist as a differentiator for one product from another. The experience aspect of a brand is a combination of consumer interaction with a brand. Brand experience is also important because a positive brand experience will encourage revisit intention and bring profits, one of which is in the hotel industry. Hotel Santika is one of the hotel brands that offer an interesting and different experience. According to its brand values, there is an Indonesian nuance as a differentiator from other hotels. The purpose of this study was to determine the effect of brand experience on revisit intention to Hotel Santika Premiere ICE BSD City. This study used quantitative research methods and data collection techniques through questionnaires to determine the relationship between the independent variables and the dependent variable. The determination of the sample was carried out based on the probability sampling approach with the simple random sampling technique. Validity test, reliability test, classical assumption test, multiple linear regression analysis test, and hypothesis test on data from 120 respondents which were processed using IBM SPSS 25th Version. The results of this study indicate that there is a simultaneous and partial influence of brand experience on revisit intention to Hotel Santika Premiere ICE BSD City; so it is advisable to maintain and improve the brand experience that has been owned by Hotel Santika Premiere ICE BSD City